Peran Manajemen Sumber Daya Manusia Dalam Pendidikan - Dyna Rahayu Natalina Sibarani; Nuraini Taraigan; Amini Amini; Heldy Petra Meliala; Aswinta Ketaren; Rusnita Simanjuntak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine the role of human resource management in education. Management comes from the English word to manage, which means to organize, manage or manage. According to the term, management is the process of coordinating work activities so that they can be completed efficiently and effectively with and through other people. Based on the above, management is a way to organize or even manage something to get excellent and maximum results and get the job done optimally. Human Resources can be observed in two aspects, namely quality, and quantity. Quantity concerns the number of human resources (population) whose contribution is less critical in development than quality. Even the amount of human resources must be accompanied by good quality to avoid becoming a burden for the development of a nation. While quality concerns the quality of human resources, which involves physical and non-physical abilities (intelligence and mental). In conclusion, the goals in educational HR management include: the goals of society as a whole, the achievement of organizational goals, the achievement of functional purposes, the achievement of personal goals. Keywords: Education, Management, Human Resources